Difference in mesothelin‐binding ability of serum CA125 between patients with endometriosis and epithelial ovarian cancer. Issue 8 (17th September 2014) - Sasaki, Aya; Akita, Kaoru; Ito, Fumitake; Mori, Taisuke; Kitawaki, Jo; Nakada, Hiroshi
<x xml:space="preserve">Abstract</x> The epithelial ovarian carcinoma (EOC) is an aggressive malignant tumor, and is currently the leading cause of gynecologic cancer death. CA125 is the most commonly used serum marker for EOC, but shows a high‐false‐positive rate for several benign diseases such as endometriosis. The purpose of our study is therefore to identify a useful biochemical tool for detecting qualitative differences between CA125 from patients with endometriosis and EOC, and to facilitate differential diagnosis of these diseases. In our study, using two different CA125‐binding molecules, i.e., recombinant mesothelin and an anti‐CA125 monoclonal antibody, a novel sandwich ELISA for determining the serum levels of CA125 with mesothelin‐binding ability (CA125meso) was developed, and tested for patients with endometriosis (n = 59) and EOC (n = 36). We found that both the serum CA125meso level and the ratio of the serum CA125meso to CA125 levels (CA125meso/CA125) were significantly higher in patients with EOC than in patients with endometriosis (p < 0.00005 and p < 0.000001, respectively). Furthermore, receiver operating characteristic analysis showed that the CA125meso assay was superior to the conventional antibody‐based CA125 assay in discriminating endometriosis from EOC. Thus, mesothelin‐binding ability may be a useful indicator for qualitatively evaluating CA125 in patients with endometriosis and EOC.